Revisiting the causal nexus between coal energy consumption, economic growth, and pollutant emission: sorting out the causality - Joshua, Udi; Uzuner, Gizem; Bekun, Festus Victor (Springer Heidelberg, 2020)
Anthropogenic activities in search of livelihood come with its environmental implications. This is in line with the current crusade of the United Nations sustainable development goals (SDGs) target 7 and 13 for effective clean energy access and mitigating the adverse effect of climate change issues. Since the seminal study of Kraft and Kraft (1978) on the nexus between energy and gross national product, there has been no consensus in the extant literature in the last four decades. To this end, the current study applies recent data for the case of Nigeria from 1970 to 2017 on an annual frequency. Modified Wald causality test of Toda-Yamamoto is in conjunction with the recent gradual shift causality test with Fourier approximation for robustness and precision of analysis. Empirical results show the pollutant driven economy as one-way causality is seen running from pollutant emission to economic growth. This suggests that economic growth is driven by dirty energy sources that are from non-renewable energy sources. This is further validated in the pollution haven hypothesis (PHH) confirmed in the study by the causality seen running from foreign direct investment and carbon dioxide emissions. Additionally, the exploration of natural resources also engenders economic expansion in Nigeria. Based on the current study findings, a couple of submissions are made such as the need for a paradigm shift to cleaner energy sources. More so, the need for the adoption of cleaner, eco-system friendlier innovations, and technologies will aid in the attainment of the SDGs of mitigating climate and pollution issues.
Keywords: Coal energy consumption; Economic growth; Pollutant emission; Nigeria; C32; C23; Q5